2019
DOI: 10.3201/eid2510.190700
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis in the Highlands of Madagascar, 2013–20171

Abstract: Sporotrichosis is a saprozoonotic fungal infection found mostly in tropical and subtropical areas. Few case reports in Madagascar have been published. To document sporotrichosis epidemiology in Madagascar, we conducted a cross-sectional study. During March 2013–June 2017, we recruited from select hospitals in Madagascar patients with chronic cutaneous lesions suggestive of dermatomycosis. Sporotrichosis was diagnosed for 63 (42.5%) of 148 patients. All but 1 patient came from the central highlands, where the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…However, these studies did not specify any previous treatments received by patients before inclusion. In addition, it has been reported that the clinical presentation of CBM does not appear to differ according to fungal species (Bonifaz et al, 2001), an observation that we confirmed in our entire cohort of 50 patients recruited from 2013 to 2018 (Rasamoelina et al, 2019). Our study showed that previous treatment may change the appearance of the lesions, which appeared smoother and shinier, less warty, less squamous, pink, and completely depigmented.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, these studies did not specify any previous treatments received by patients before inclusion. In addition, it has been reported that the clinical presentation of CBM does not appear to differ according to fungal species (Bonifaz et al, 2001), an observation that we confirmed in our entire cohort of 50 patients recruited from 2013 to 2018 (Rasamoelina et al, 2019). Our study showed that previous treatment may change the appearance of the lesions, which appeared smoother and shinier, less warty, less squamous, pink, and completely depigmented.…”
Section: Discussionsupporting
confidence: 85%
“…A prospective descriptive study of patients with clinically suspected CBM or another chronic dermatomycosis was performed (Rasamoelina et al, 2019) (De Pauw et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…3) [109]. Outside the main transmission area in South Africa, sporadic cases have been reported in Madagascar [116], Zimbabwe [117], Nigeria [118] and Sudan [119]. Surprisingly, the HIV/AIDS epidemic in South Africa does not appear to be associated with a concomitant increase in sporotrichosis cases, which remain infrequent [120,121].…”
Section: The Geography Of Sporothrix and Sporotrichosismentioning
confidence: 99%
“…
We conducted a cross-sectional study as described (12). We recruited patients with clinically suspected chromoblastomycosis or another chronic dermatomycosis during March 2013-June 2017 at the Dermatology Department of the Joseph Raseta Befelatanana University Hospital in Antananarivo or during advanced consultation campaigns in districts (Figure 1, panel A).
…”
mentioning
confidence: 99%
“…Since 2013, we have established a cross-sectional study to document the current epidemiology of implantation mycoses in Madagascar, including chromoblastomycosis (12). Clinical diagnosis and fungal identification were confirmed by using molecular biology methods.…”
mentioning
confidence: 99%